Analisis Unsur Intrinsik Puisi Pada Buku Siswa Bahasa Indonesia Dikelas 4 Sekolah Dasar - Muhammad Lukmanul Hakim; Din Azwar Uswatun; Iis Nurasiah (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2020)
This study aims to describe the intrinsic element of the fourth grade Indonesian language poetry learning material in theme 6 used by elementary schools. This type of research is a qualitative research with a qualitative descriptive approach. This research was conducted in the even semester of the academic year 2018/2019. The place of the research was SDN Cisarua 1, located at JL.Tipar Gg. Meralaya II No. 142 City of Sukabumi. This research uses quota sampling technique with the object book theme 6 My dreams are grade IV elementary school. Data collection techniques used were interview and documentation techniques which the implementers used interview and documentation guidelines to analyze the intrinsic elements of poetry material in the theme book. The results of this study are poetry learning in class IV Indonesian subjects contained in Theme 6 regarding my goals. Poetry material is explained about the meaning of poetry, the types of poetry, and the intrinsic elements of poetry. There are 7 intrinsic elements in poetry, namely theme, sound, rhyme, diction, imagination, cooperation, and rhythm.